SHRED is a regulatory cascade that reprograms Ubr1 substrate specificity for enhanced protein quality control during stress - Szórádi, Tamás; Schaeff, Katharina; Schmidt, Rolf; Bircham, Peter W.; Leiss, Kevin; Diaz-Miyar, Juan; Schuck, Sebastian (Molecular cell, 2018)
Summary - When faced with proteotoxic stress, cells mount adaptive responses to eliminate aberrant proteins. Adaptive responses increase the expression of protein folding and degradation factors to enhance the cellular quality control machinery. However, it is unclear whether and how this augmented machinery acquires new activities during stress. Here, we uncover a regulatory cascade in budding yeast that consists of the hydrophilin protein Roq1/Yjl144w, the HtrA-type protease Ynm3/Nma111, and the ubiquitin ligase Ubr1. Various stresses stimulate ROQ1 transcription. The Roq1 protein is cleaved by Ynm3. Cleaved Roq1 interacts with Ubr1, transforming its substrate specificity. Altered substrate recognition by Ubr1 accelerates proteasomal degradation of misfolded as well as native proteins at the endoplasmic reticulum membrane and in the cytosol. We term this pathway stress-induced homeostatically regulated protein degradation (SHRED) and propose that it promotes physiological adaptation by reprogramming a key component of the quality control machinery.
Gesehen am 02.05.2019